EVALUATION OF THREE CHROROPLASTIC MARKERS FOR BARCODING AND FOR PHYLOGENETIC RECONSTRUCTION PURPOSES IN NATIVE PLANTS OF COSTA RICA - Vindas-Rodríguez, Milton (2012)
DNA barcoding has been proposed as a practical and standardized tool for species identification. However, the determination of the appropriate marker DNA regions is still a major challenge. In this study, we extracted DNA from 27 plant species belonging to 27 different families native of Costa Rica, amplified and sequenced the plastid genes matK and rpoC1 and the intergenic spacer trnH-psbA. Bioinformatic analyses were performed with the aim of determining the utility of these markers as possible barcodes to discriminate among species and for phylogenetic reconstruction. From the markers selected, the trnH-psbA spacer was the most variable in terms of genetic distance and the most promising region for barcoding. However, it presented a limited use for constructing phylogenies due to the complexity of its alignment. The locus matK was less variable but was also useful for species discrimination and for phylogenetic tree generation. The rpoC1 region was highly conserved and suitable for phylogenetic studies, but presented a limited utility as a barcode. The marker combination matK and rpoC1 provided the best resolution for establishing valid phylogenetic relationships among the analyzed plant families. In conclusion, more than one marker should be used for plant barcoding purposes, to provide complementary and variable information for the interespecific species discrimination.